Methods for estimating petrophysical parameters from well logs in tight oil reservoirs: a case study. (29th January 2016) - Zhao, Peiqiang; Zhuang, Wen; Sun, Zhongchun; Wang, Zhenlin; Luo, Xingping; Mao, Zhiqiang; Tong, Zemin
Abstract: Estimating petrophysical parameters from well logs plays a significant role in the exploration and development of tight oil resources, but faces challenges. What's more, the methods for petrophysical parameters from well logs are paid little attention at present. In this paper, the typical tight oil reservoirs of Northwest China are used as an example. Based on the characteristics of mineralogy and fluids in the study field, the rock is assumed into five components which are clays, quartz and feldspar, carbonates, kerogen and pore fluids (porosity). The sum of kerogen content and porosity is defined as the apparent porosity. Then, two porosity log response equations are established. Once the clay content is determined by an individual method, the quartz and feldspar content, carbonate content and apparent porosity are calculated through the established equations. The kerogen content is the difference of the apparent porosity and porosity from nuclear magnetic resonance (NMR) logs. This paper also presents a new approach that combines the complex refractive index method (CRIM) and pseudo Archie method to compute saturation from dielectric logs, which avoids selection for the dielectric constants of each of the minerals. The effectiveness and reliability of these methods are verified by the successful application in the study of the target tight oil play in Northwest China.